NUMERICAL EVALUATION OF THE EFFECT OF UNCERTAINTIES IN ROTATING MACHINERY USING REDUCED MODEL - Costa, Tatiane Nunes da; Gonçalves, Daniel Ferreira; Borges, Romes Antonio (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
Rotating machines are extensively used in industrial applications considering the flexibility of the equipment, capable of being operated at extreme speeds, the study of uncertainties are required, due the influence in the dynamic behavior. The use of stochastic techniques have played an important function in engineering problems, the Monte Carlo method (MC) and your variant called Latin Hypercube (LHS) are widely used to model u ncertain parameters. In this context, the present work is devoted to analysis of the uncertainties in the parameters of a flexible rotor discretized by finite element (FE). Aiming a considerable saving of time, models reduced by Iterative Improved Reduction System (IIRS) method were used in the numerical analysis process. The analysis procedure is limited to the frequency domain. Solution envelopes are obtained by LHS method that allow us to describe the system behavior considering some parameters as random.